YouTube as a Supplementary Resource for Learning English Speaking and Conversation of Non-English Department Students - Nur Fitria, Tira (LingPoet: Journal of Linguistics and Literary Research, 2025)
This study explores non-English department students' perceptions of the use of YouTube videos as supplementary resources in learning English speaking and conversation. This research is descriptive qualitative research. The analysis shows that non-English students generally find YouTube an engaging and effective tool for learning English. They appreciate its flexibility, accessibility, and the realistic learning experiences it offers. YouTube is particularly valued for improving understanding of English topics and conversations, providing cultural insights, and supporting pronunciation and intonation. It is seen as a personalized and enjoyable learning resource. YouTube is regarded as effective for vocabulary acquisition. Students believe it helps them learn new words, understand word usage in social contexts, and apply vocabulary in real-life conversations. The platform’s clear explanations and frequent phrase repetition improve retention and confidence. In speaking skills, YouTube has a significant impact. It enhances pronunciation, builds confidence, and helps students feel more comfortable speaking English, especially in casual situations. Students get benefits from exposure to various accents and conversation examples, which help improve fluency. However, students face several challenges using YouTube for learning, such as difficulty understanding accents or fast speech, poor video/audio quality, and trouble maintaining focus. There is also a challenge in selecting appropriate videos, and some students feel there is insufficient explanation of vocabulary or a lack of interactive speaking practice. Students suggest several improvements to make YouTube more effective as a learning tool, including the addition of subtitles, more videos on formal and professional conversations, and better video selection guidance. They recommend incorporating interactive quizzes, visuals, and more tailored conversation examples for different learning needs. Additionally, they suggest videos should focus on correcting pronunciation errors and include more exposure to diverse accents. Lastly, students call for guided speaking practice sessions to enhance learning. Overall, students highlight YouTube’s potential as an effective and flexible tool for English learning while offering suggestions to overcome its challenges and enhance its educational value.